O frete de retorno nas ferrovias regionais de cargas brasileiras caso Ferrovia Transertaneja - Bastos, Luís Othon (2022)
In the first chapter of this work, we investigated the reasons why the return rail freight was not included in the design or operation of the Brazilian regional freight railroads, which is used only as corridors for the export of ore and agribusiness from the hinterland to the coastal ports. We also question the reasons why these railroads do not act as an instrument for improving the socioeconomic conditions of their area of influence or national integration. In our bibliographical research and interviews with academics, consultants and government managers and companies that operate in the railroad sector pointed out several reasons why railroad projects and operators consider regional freight railroads in Brazil only as export corridors for agricultural commodities. and minerals. In the second chapter, we approach a preliminary study about the viability of the return freight (west/east direction) on the Ferrovia Transertaneja, a railway line in the implementation phase and whose trajectory will cut longitudinally throughout the state of Pernambuco. The Transertaneja Railroad was designed to transport minerals from the hinterland of Pernambuco and Piauí to the port of Suape in Pernambuco state. The study preliminarily assessed the viability of the cargo transport operation, return freight, as a complementary activity to commodity transport, with a favorable financial result and greater use of the permanent railway track.